Flavor enhancers in growing-pig rations - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Groups of growing pigs restricted to control feed or feed containing one of 5 commercial flavoring agents or taste enhancers consumed similar amounts of feed and made similar weight gains and similar feed/gain.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Flavor enhancers; Weight gain; Feed/gain ratio